The identification of STAT2 as a pervasive negative regulator of STAT1 activity and cytokine signalling - Ho, Johnathan (2018)
Interferons (IFNs) are cytokines which play a crucial role in the host defence against pathogens through the upregulation of hundreds of target genes. The binding of an IFN molecule to its specific receptor, results in the tyrosine phosphorylation of a member of the Signal Transducer and Activator of Transcription (STAT) protein family, a process often termed ‘STAT activation’. The first observation of this mechanism was the discovery of STAT1 and STAT2, which are both activated in response to type-I interferon and form a DNAbinding heterodimer which acts as a transcription factor. In the 25 years since this breakthrough, the establishment of these proteins as partners in signal transduction has been shown repeatedly. Whilst STAT1 has since be found to act as a signal transducer for many different cytokines, STAT2 appears to be almost exclusively driven by type-I IFN. Nonetheless, STAT2-deficient phenotypes suggest a broader and IFN-independent role for this protein. This thesis focused on the role of the STAT N-domain, which has been recently identified as an important site for cytokine-independent interactions. Using a variety of methods, including fluorescence microscopy as well as biochemical and biological assays, STAT2 was shown to be constitutively bound to STAT1 via their N-domains. The consequence of this binding was a strong inhibitory effect on the activity of STAT1. This was attributed to the formation of semi-phosphorylated dimers which were excluded from entering the cell nucleus. Furthermore, a single residue was found to abrogate this interaction and resulted in a hyper-responsive STAT1 phenotype in several immune responses such as parasitic immunity, antigen presentation and senescence. Therefore, STAT2 should now be considered an innate negative regulator of STAT1 activity in all cytokine signalling pathways with the exception of type-I interferon.